2014
DOI: 10.1002/zaac.201400223
|View full text |Cite
|
Sign up to set email alerts
|

In Operando GIXRD and XRR on Polycrystalline In52Pd48

Abstract: A combined approach of grazing incidence X-ray diffraction (GIXRD) and X-ray reflectivity (XRR) under in operando conditions on polycrystalline materials is presented. This approach allows tracking of material changes of amorphous or crystalline nature in the nearsurface region. Crystalline phases formed in operando can be identified by X-ray diffraction, while by XRR measurements information about the thickness and the density of overlayers is obtained. The setup also allows collection of data generated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…These isotope-labeling experiments prove the active contribution of oxygen from the catalytic material during MSR in the form of a reactive InPd/In 2 O 3 interface. This is strongly supported by operando studies on In-rich bulk InPd, where the formation of an InPd/In 3 Pd 2 /In 2 O 3 surface structure was identified . These results strongly suggest that the intermetallic compound is not the active site, but apparently, an active redox chemistry at the phase boundary of oxide and intermetallic compound is responsible for the high CO 2 selectivity of these catalytic materials and should be observable by the formation of different intermetallic compounds.…”
Section: Resultsmentioning
confidence: 99%
“…These isotope-labeling experiments prove the active contribution of oxygen from the catalytic material during MSR in the form of a reactive InPd/In 2 O 3 interface. This is strongly supported by operando studies on In-rich bulk InPd, where the formation of an InPd/In 3 Pd 2 /In 2 O 3 surface structure was identified . These results strongly suggest that the intermetallic compound is not the active site, but apparently, an active redox chemistry at the phase boundary of oxide and intermetallic compound is responsible for the high CO 2 selectivity of these catalytic materials and should be observable by the formation of different intermetallic compounds.…”
Section: Resultsmentioning
confidence: 99%
“…In a similar temperature regime (723 K) and under reactive atmosphere (presence of methanol and water), experiments on a polycrystalline In-Pd sample have shown that indium segregates to the surface forming In 2 O 3 . 50 The stability of InPd bimetallic particles under oxidation conditions has also been tested and it was shown that the particles fully decompose into Pd and In 2 O 3 already at 573 K. 51 To further understand the trends observed experimentally for the (100) and (111) surfaces, we have performed additional calculations not reported previously. The surface energies of the non-stoichiometric (100) and (111) surfaces have been evaluated by DFT calculations.…”
Section: Discussionmentioning
confidence: 99%
“…[16] The formation of oxide layers on the intermetallic particles was also identified for GaPd 2 [7] and the InÀ Pd system. [13,[24][25][26] Especially for In 2 O 3 -containing materials, the role of partially reduced species or oxygen vacancies was additionally investigated in the hydrogenation of CO 2 to methanol, [27,28] the reverse reaction of MSR. This emphasizes the complex nature of catalytic materials consisting of oxide-supported intermetallic compounds.…”
Section: Introductionmentioning
confidence: 99%